NATRIUM DIKLOFENAK UNTUK PENGOBATAN NOKTURIA YANG DISEBABKAN OLEH NOCTURNAL POLYURIA - Sunarno, Eddy; Alif, Sabilal; Hardjowijoto, Sunaryo; P, Widodo J (Indonesian Urological Association, 2009)
Objective: To investigate the efficacy of diclofenac 50 mg (Non-Steroidal Anti-Inflammatory Drug) in the treatment of nocturnal polyuria. Materials and methods: Twenty four patients (23 male and 1 female) with a mean age of 61 years (range 34 – 80) diagnosed with nocturnal polyuria were recruited. The study period comprised 2 weeks of either placebo or active medication. Following one-week rest period, patients were crossed over to the other medication for a further 2 weeks. Frequency volume charts were completed during the second week of each of the two study periods along with feedback forms to assess any subjective improvement in symptoms during each of the study periods. Results: A significant improvement in the symptoms was noted for diclofenac when compared with the placebo. The mean nocturnal frequency decreased from 3,61 ± 2,45 to 2,39 ± 1,1 (p<0,05) and the mean 24 h urine volume decreased from 1139,64 ± 365 to 1089 ± 324 (p>0,05), but there is no statistically different. No significant side effects were reported. Conclusion: Natrium diclofenac 50 mg are effective in the treatment of nocturnal polyuria causing a decrease in nocturnal frequency with subjective symptom improvement. Our study suggests, Natrium diclofenac not to prolonged treatment. Further research to find the alternative treatment is recommended.